Analisis Komunikasi Pemasaran Terpadu PT. Cubes Consulting dalam Membangun Brand Association - Sherly Margaretha; Widayatmoko Widayatmoko; Muhammad Adi Pribadi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2012)
This study discusses the integrated marketing communications conducted by PT Cubes Consulting to build the brand image of the company. Authors take this subject because the authors assume that the PT Cubes Consutlting as an SAP partner, a company that is still very new, but it could have a considerable client references and come from large companies. Though competition in the business world is not easy, because many SAP partners in Indonesia who have first foray into the world and be seen from the size of the business, obviously bigger.